CRX-linked macular dystrophy with intrafamilial variable expressivity. (3rd September 2018) - Romdhane, Khaled; Vaclavik, Veronika; Schorderet, Daniel F.; Munier, Francis L.; Viet Tran, H.
ABSTRACT: Background : We present a macular dystrophy of differing severity in a single kindred caused by a heterozygous nonsense mutation in CRX . Case report : A 21-year-old Caucasian male from a Swiss family was investigated for decreasing central visual acuity associated with dischromatopsia. Clinical examination revealed posterior pole atrophy, including the maculopapillary bundle. Multimodal imaging, including autofluorescence, showed a hyperautofluorescent paramacular ring in both eyes. Genetic analysis identified a c.313C>T, p.Q105* nonsense mutation in CRX . The same mutation was identified in his father and uncle. Both of them showed signs of the disease, however with different severity. Conclusion : We describe an intrafamilial variable expressivity of a CRX mutation causing an isolated macular dystrophy.